Bedaquiline Efficacy in the Russian Federation: Meta-analysis with a Random Effects Model - A. A. Starshinova; I. F. Dovgalyuk; N. N. Osipov; D. A. Kudlay (Туберкулез и болезни лёгких)
The objective: to determine the rate of treatment success in MDR and XDR pulmonary tuberculosis patients when treated with chemotherapy regimens containing bedaquiline based on a meta-analysis using mathematical modeling.Subjects and Methods. We searched and analyzed published studies of bedaquiline conducted from 2014 to 2022 in the Russian Federation. A total of 41 publications were found, of which 15 were included in the meta-analysis since they contained data eligible for analysis. They presented treatment results of 1,356 TB patients, 886 (65,3%) patients had MDR TB, and 470 (34,7%) had XDR TB (according to the definition as of 2020). All of them received bedaquiline within the standard regimen for 24–26 weeks.Results. According to the meta-analysis results, when using treatment regimens containing bedaquiline in MDR/XDR TB patients, sputum conversion was achieved in 79,6% (95% CI 75,1–83,4) of cases, and effective treatment was observed in 82,0% (95% CI 78,6–84.9) of cases. Treatment default was noted in 8,7% (95% CI 5,7–13,1) of cases. At the same time, there is a statistically significant relationship (p<0,01) between the proportion of patients with comorbidities and the proportion of patients with incomplete treatment. Lethal outcomes were recorded in 5,8% (95% CI 3,6–9,2), which were associated with the severe course of tuberculosis and concomitant pathology. Bedaquiline was canceled in 7,8% (95% CI 4,0–13,5) of cases. When analyzing the data of patients with MDR TB and XDR TB separately, treatment efficacy differed and amounted to 89,9% (95% CI 85,9–92,9) versus 71,9% (95% CI 66,3–76,8), respectively.